Annealing of Strontium Titanate Based Thermoelectric Materials by Graphite: Mechanistic Analysis by Spectroscopic and Chromatographic Techniques. Issue 4 (14th April 2020) - Lee, Alex Chinghuan; Qin, Mengjie; Li, Haoran; Shi, Zongmo; Xu, Jie; Gao, Feng; Chen, Yongsheng
Abstract: Strontium titanate (SrTiO3 ) based materials are promising for high‐temperature thermoelectric applications. In order to enhance their performance, annealing is usually required and carried out under various atmospheres. Annealing with graphite is quite effective, but the mechanism is not yet clear. In this work, we use IR spectroscopy and gas chromatography (GC) to monitor the chemical environment under the annealing conditions (1350 °C for 8 h under 16.9 mL/min N2 with graphite) and quantify the various gases evolved in the process. It is shown that reducing agents, H2 and CO (concentrations peaked at ca. 0.4–0.5 %), are generated from graphite in the annealing process. H2 is produced in carbon gasification reaction, which also generates CO. Additional CO is produced from incomplete combustion of carbon. In the annealing of a La‐doped SrTiO3 ‐based ceramic with graphite, higher levels of H2 O and CO2 are detected, which is resulted from the reduction of the ceramic by H2 and CO, respectively. About 67 % of the oxygen vacancies were created by CO reduction while about 33 % by H2 reduction. The conclusions are well supported by direct weight loss measurements with a difference of less than 6 %. Abstract : Revealing annealing : The annealing mechanism of SrTiO3 based ceramics using graphite has been elucidated. This process occurs through the reducing agents H2 and CO, which are generated from the gasification reaction in the annealing process. Additional CO is produced by incomplete incomplete combustion of carbon. This mechanistic study suggests that more reducing agents can be used in the annealing process, and the process can be controlled by manipulating the chemical environment.